WEB APPLICATIONS FOR LEARNING JAPANESE FOR SCHOOL CHILDREN USING Macromedia Dreamweaver - Reza Kautsar; Marzuki Marzuki., SKom., MMSI (Jurnal Sistem Informasi, 2007)
Internet is now a become a most effective option in disseminating information, because the Internet has a range of very large networks. One of the  information  received  great  places  on  the  Internet  include  information  relating  to education, especially the Japanese language education. This information is conveyed through one of the storage media of information on the Internet Web site. Japanese language is the language of the world. In all areas, especially areas information  technology,  all  using  the  Japanese  language.  Japanese  language  should  be introduced at an early age, so that in future the children into the next generation of achievers. Scientific writing is trying to explain how the development of a Web site about Japanese language learning. Starting from design stage to design the Web site ready to be published on the Internet. All were created using Macromedia Dreamweaver MX software.